(3GdCTQHI hGdeYGLjf hGdeQGge hGdCcMGds - (3CHh GdaVd eMeO Hf GdbGSe GdYLdGfjs
(3ChdgG (B:s
(3jbhd CHh GdaVd GdYLdGfi CeG HYO MeO Gddg hGdUdGI Ydi QShdg aEfg Je GdeLehY GdPi bUOJ Ef gPG GdcJGH eQJH Ydi KdGKI YTQ HGHkG s
(3BNQgG (B:s
(3eHJhQ GdBNQ , hBNQ GdehLhO efg (B: (3hjJVGYa aJcKQ GdMejGJ GdegdcI hcKQI GdYeQGf HSHH GdJYaf hGdQWhHGJ GdaGSOI QYGjI s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B23 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs